The mirror crack'd - Christie, Agatha, 1890-1976. (New York : Signet, 2000)
Miss Jane Marple investigates the poisoning death of a fan of Marina Gregg, the film star who recently took up residence in St. Mary Mead and may have been the killer's intended target.
"Previously published as The mirror crak'd from side to side.".
Young Adult
Keywords: Marple, Jane (Fictitious character) -- Fiction; Motion picture actors and actresses -- Fiction; Actors -- Fiction; Marple, Jane (Fictional character) -- Fiction; Mystery fiction